If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(1 + 2c) = -91 (1 * -7 + 2c * -7) = -91 (-7 + -14c) = -91 Solving -7 + -14c = -91 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -14c = -91 + 7 Combine like terms: -7 + 7 = 0 0 + -14c = -91 + 7 -14c = -91 + 7 Combine like terms: -91 + 7 = -84 -14c = -84 Divide each side by '-14'. c = 6 Simplifying c = 6
| [5X+9]+16=2 | | 2x+(3x+2)= | | 15=x-7+2x-17 | | 8x+7-x=-2-5 | | M+3+8=80 | | 2x+1.50y=90 | | 9x(x-3)=(2x+4)(x-3) | | 6x+20=10.20x | | 8(6a+7)= | | 5x-3(x+3)=-17+6x | | 5s+10t=9 | | Ln(8x)=253 | | 70=p-10 | | x/3-12=20 | | 12=8-x/5 | | 10d-7d-2d=19 | | 14=6y | | 4x(x-3)=(2x+1)(x-3) | | 3(y+7)-5y= | | 7/8-3k | | 3x+4=x+11+13 | | 10d-7d-2d= | | y-0.18y= | | 9x-4=-2x+7 | | y-1=2(x-3-2) | | 6ax-10ay+3x-5y= | | 3/83/7 | | 15=x-2+3x-15 | | -4+7y-3y-5= | | (X^2-x)/2=36 | | N-8.09=-0.06 | | .45x=5+.40x |